The relevance of corporate social responsibility for a sustainable human resource management: An analysis of organizational attractiveness as a determinant in employees' selection of a (potential) employer - Bettina Lis (Management Revue, 2012)
Corporate Social Responsibility (CSR) has become a central issue of business management in recent years. This study aims to add to the literature by pointing out the relevance of CSR for a Sustainable Human Resource Management (HRM). In particular this research investigates job seekers' perceptions of CSR. The paper focuses on the importance of CSR with in the process of selecting potential employers by analyzing the impact of four different CSR-dimensions upon organizational attractiveness. To address this issue, a policy-capturing study was conducted. Generally the paper provides evidence that each aspect of CSR has a specific effect on organizational attraction. Referring to Sustainable Management the study reveals that CSR seems to be an effective tool to attract potential employees. If organizations are willing to provide Sustainable HRM practices they can become an employer-of-choice.
Keywords: J24; M12; M14; M50; 650; corporate social responsibility; Sustainable Human Resource Management; organizational attractiveness; prospective employees; sustainability